Efficacy of hemoadsorption in the severe course of COVID-19 - Yakovlev, Aleksei Yurievitch; Ilyin, Yuri Vladimirovitch; Bershadsky, Feodor Feodorovitch; Selivanov, Dmitry Dmitrievitch; Pevnev, Aleksei Aleksandrovitch; Trikole, Artur Igorevitch; Popov, Aleksander Yurievitch; Pisarev, Vladimir Mitrofanovich (Frontiers in Medicine, 2025)
IntroductionInsufficiencies of the majority of targeted therapies for the most severe, life-threatening forms of COVID-19 warrant alternative, adjuvant treatment options for enhanced life maintenance that include extracorporeal blood purification and homeostasis support. The goal of the current study is to evaluate the clinical efficacy of hemoadsorption with mesoporous hypercrosslinked polystyrene beads (Efferon CT single-use cartridge) in an expanded cohort of patients with severe and critical COVID-19 resistant to antibody therapies and requiring post-therapy invasive mechanical lung ventilation (MLV) versus parameter-matched control group with no hemoadsorption.Materials and methodsA single-center cohort study (NCT06402279) enrolled patients from October 2020 to February 2022: the Efferon CT group (non-responders to anti-cytokine antibody therapy requiring IMV, hemadsorption, and standard treatment, n = 65) and retrospectively acquired propensity-matched control group (no hemadsorption, standard treatment only, n = 65).ResultsThis observational study revealed the capability of Efferon CT hemoadsorption to safely, rapidly, and significantly reduce the need for norepinephrine, increase the oxygenation index, prevent the sepsis-associated AKI, decrease the development of multiorgan failure, and restore the immune system balance by decreasing pro-inflammatory IL-6, ferritin levels, and neutrophil-to-lymphocyte ratio.ConclusionThe clinical efficiency of hemoadsorption using Efferon CT was confirmed by the resolution of acute respiratory failure in 54% of patients, significantly increasing the number of days without mechanical ventilation and increasing early the index of oxygenation. Most importantly, the hemoadsorption with Efferon CT was safe and resulted in a significant decrease in the mortality of severe COVID-19 patients.Clinical trial registrationwww.clinicaltrials.gov, Identifier NCT06402279.